Challenging Tendering-Phase Factors in Public Construction Projects—A Delphi Study in Saudi Arabia - Nawaf Alahmadi; Mohammed Alghaseb (Buildings, 2022)
Public construction projects in Saudi Arabia are fraught with several challenges threatening open and fair competition, which consequently negatively influence the decision of contractors to participate in bidding. Nevertheless, the construction sector has witnessed rapid reforms since 2016, which have resulted in the issuing of new legislation and regulations as well as the creation of governing bodies. Hence, the concept of open and fair competition plays a significant role in the governance of these challenges in the upstream process of construction tendering. Therefore, this paper explores challenges that are hindering contractors’ participation in the tendering phase of public construction projects in light of these new legislations and authorities. Twelve challenging factors were identified from a structured literature review of previous relevant empirical studies available in online search engines since the 1980s. Those factors were measured through Delphi survey questionnaires, which provided respondents with the option of adding new challenging factors. Thus, twenty factors were identified. A descriptive method was used to determine and prioritize these challenging factors. The survey findings indicate that the most influential hindering factors are (1) awarding contracts based on the lowest bidder, (2) inadequate or incomplete specifications, (3) poor contract documents, and (4) poor cost-estimating practices. These findings are vital in exposing the lack of relationships between the construction industry, regulators, and stakeholders for robust partnerships, thereby helping to ensure the fair participation of contractors, which boosts open and fair competition concepts for public construction projects.